Competence and Training as Determinants of Employee Performance: The Mediating Role of Organizational Commitment at the Department of Industry and Trade of Malinau Regency - Steven, Yulius; Hasyim, Budi; Wijayanti, Asih Kusuma; Kaujan, Kaujan; Ardiansyah, Riyans; Aswan, Aswan (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the effects of competence and training on employee performance, with organizational commitment serving as a mediating variable, in the Department of Industry and Trade of Malinau Regency. The research background focuses on various issues related to employee performance, including limitations in technical competence, suboptimal training effectiveness, and variations in employees’ levels of commitment to carrying out public service duties. The Resource-Based View (RBV) theory is employed to explain how competence and training enhance organizational capabilities. This study uses a quantitative, path-analytic approach to examine both direct and indirect relationships among variables. The results indicate that competence and training have a significant effect on employee performance, both directly and indirectly through organizational commitment as a mediating variable. These findings highlight that performance improvement is not solely dependent on employees’ technical skills and knowledge, but also on their level of psychological attachment to the organization. In addition to contributing theoretically to the field of human resource management, this study provides practical recommendations, including developing needs-based training programs, strengthening organizational culture, and implementing sustainable competency development policies to improve employee performance in local government institutions.